Interprofessional Education: An Exploration in Physical Therapist Education. Issue 2 (2015) - Wise, Holly H.; Frost, Jody S.; Resnik, Cheryl; Davis, Beth P.; Iglarsh, Annette Z.
Abstract : Background and Purpose. : Interprofessional education (IPE) has been a topic of national and international discussion for several decades. The recent development of the Interprofessional Education Collaborative (IPEC) Core Competencies prompted the American Council on Academic Physical Therapy (ACAPT) to consider ways the physical therapy profession could become more involved. In 2013, the ACAPT Board of Directors appointed a 4‐person task force to: (1) compile, collect, and analyze data on current and projected IPE initiatives in physical therapist education programs; (2) develop a means to disseminate information on IPE among these programs; and (3) recommend ways for physical therapists to collaborate with other health care practitioners. Outcomes. : Data was collected from representatives from each of the 209 ACAPT member institutions. Based upon the findings, at least 62 (58.5%) of the 106 (50.7%) respondents reported that IPE is a focus of their physical therapist education curriculum. Eighty respondents (75.5%) identified up to 3 reasons for the success of their initiatives. Faculty buy‐in/champions was the most frequently cited reason followed by institutional support, student support, curriculum, and external factors, respectively. The majority of respondents (n = 56) did not identify a collaborative practice partnership in which their students obtain interprofessional experience. Discussion and Conclusion. : Based on the work of national and international organizations and forums, and the results of this survey, physical therapist education programs developing IPE within their institutions typically elect to first target IPE within classroom experiences before integrating IPE within clinical experiences. In order to advance IPE within clinical experiences, development of more formalized clinical partnerships will be needed to better enable the expansion of IPE within patient care experiences for learners. This study raised additional research questions for future investigation.